Contribution of men who have sex with men (MSM) attending due to contact tracing to the diagnoses of HIV, syphilis and gonorrhoea in MSM from a clinic-based population. (27th August 2021) - Samarasekara, Keshinie; Ringshall, Miriam; Parashar, Kuhuk; Pickering, Alice; Buss, Zoe; Nichols, Kayleigh; Devlin, John; Fitzpatrick, Colin; Williams, Deborah; Richardson, Daniel
Abstract : Objectives: Rates of HIV, syphilis and gonorrhoea have increased over the past 20 years in men who have sex with men (MSM). Contact tracing strategies have increased the number of MSM attending clinics as sexual contacts. Understanding the outcomes of contact tracing could inform future public health policies to reduce the burden of STIs in MSM. Method: We aimed to describe the contribution of MSM attending as notified sexual contacts of patients with HIV, syphilis and gonorrhoea to the overall diagnoses of HIV, syphilis and gonorrhoea in MSM in a cross-sectional study. We collected data on all MSM diagnosed with HIV, syphilis and gonorrhoea in 2019 and evaluated which of these MSM were tested due to attending as a sexual contact. Results: Sexual contacts of HIV, syphilis and gonorrhoea contributed to 20% (95% CI=17.3% to 23.7%) of all diagnoses of HIV (3 of 30, 10%), syphilis (28 of 183, 15%) or gonorrhoea (98 of 420, 23%) in the study period. Asymptomatic sexual contacts contributed to 12% (95% CI=9.6% to 14.9%) of all diagnoses of HIV (3 of 30, 10%), syphilis (16 of 183, 9%) and gonorrhoea (57 of 420, 14%). The proportion of MSM diagnosed with gonorrhoea attending as sexual contacts of gonorrhoea (21%) was significantly greater than MSM diagnosed with HIV, attending as sexual contacts of HIV (3%) or MSM diagnosed with syphilis, attending as a sexual contact of syphilis (4%) (p<0.001). Furthermore, the proportion of MSM diagnosed with syphilis, attending as a sexual contact of another STI (11%) was significantly greater than MSM diagnosed with HIV, attending as a contact of another STI (7%) or MSM diagnosed with gonorrhoea, attending as a sexual contact of another STI (2%) (p<0.001). Conclusion: Contact tracing contributes significantly to the overall diagnoses of HIV, syphilis and gonorrhoea including asymptomatic sexual contacts in our population. Further efforts to increase the yield from contact tracing may continue to reduce the burden of HIV, syphilis and gonorrhoea within sexual networks of MSM.